COMPUTER PARTS AND THEIR USAGE TECHNIQUES - Matchonov Akmal (Prospects for innovative technologies in science and education, 2025)
This article provides detailed information about the main parts of a computer, their functions, and proper usage techniques. Since a computer has become an integral part of modern life, it is important to know its structure and follow the rules of maintenance.